2012
DOI: 10.3390/v4050654
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Long-Term Effect of Air Filtration on the Occurrence of New PRRSV Infections in Large Breeding Herds in Swine-Dense Regions

Abstract: Airborne transmission of porcine reproductive and respiratory syndrome virus (PRRSV) is a risk factor for the infection of susceptible populations. Therefore, a long‑term sustainability study of air filtration as a means to reduce this risk was conducted. Participating herds (n = 38) were organized into 4 independent cohorts and the effect of air filtration on the occurrence of new PRRSV infections was analyzed at 3 different levels from September 2008 to January 2012 including the likelihood of infection in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…We chose PRRSV because of its economic impact in swine industry [ 14 ]. Moreover, several studies had already demonstrated the efficacy of some air filter methods in reducing PRRSV under experimental conditions [ 1 , 15 – 17 , 6 ]. Further experiments were performed using bovine enterovirus 1 (BEV, strain LCR-4) as a surrogate for foot-and-mouth disease virus (FMDV).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose PRRSV because of its economic impact in swine industry [ 14 ]. Moreover, several studies had already demonstrated the efficacy of some air filter methods in reducing PRRSV under experimental conditions [ 1 , 15 – 17 , 6 ]. Further experiments were performed using bovine enterovirus 1 (BEV, strain LCR-4) as a surrogate for foot-and-mouth disease virus (FMDV).…”
Section: Methodsmentioning
confidence: 99%
“…Investigations on American farms equipped with air filtration revealed high efficacy in reducing the number of PRRSV outbreaks. The incidence of new PRRSV infections in breeding herds housed without air filtration was reported to be eight times higher compared to filtered farms [ 6 ]. However, commercial swine buildings with supply air filtration are still not a standard.…”
Section: Introductionmentioning
confidence: 99%
“…a condition in which clinical signs of PRRS are absent in the breeding-herd population, and PRRSV is no more transmitted from sows to their offspring ( 13 ). After reaching this preliminary status, eradication may be possible by herd closure ( 14 ), which is eased by proper air filtration devices to prevent airborne infection ( 15 ). In addition to management and biosecurity measures, various immunological approaches (vaccination and/or “conditioning” to circulating PRRSV strains) are also used for control of both respiratory and reproductive disease ( 6 ).…”
Section: The Diseasementioning
confidence: 99%
“…While data exist regarding the ability of the virus be transported via aerosols up to 9.2 m [ 9 ], little is known about the dynamics of daily PRRSV airborne challenge directly at the farm level. If the level of airborne PRRSV challenge on a day-to-day basis could be documented, decisions regarding the application of intervention strategies capable of reducing the airborne risk (e.g., area vaccination or air filtration) would be easier to make [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%